The Mechanism of T Cells in the Microenvironment of Triple Negative Breast Cancer and the Application Potential of Immunotherapy - Qiao, Jiayue; Wu, Furong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Triple negative BC (TNBC) is a malignant tumor with high invasion, high incidence rate and poor prognosis. The mechanism of T cells in its microenvironment and the potential application of immunotherapy have become the focus of current research. Research has shown that the tumor microenvironment of TNBC is highly heterogeneous, and T cells, as core members of the immune system, play a crucial role in the anti-tumor process by recognizing and clearing tumor cells. However, T cell activity is often suppressed by ICs such as PD-1/PD-L1, leading to tumor immune escape. With the development of single-cell RNA sequencing technology, there is a deeper understanding of the functional status of T cells in the TNBC microenvironment. Meanwhile, IC inhibitors (ICIs) and adoptive cell immunotherapy have shown significant potential in the treatment of TNBC. For example, PD-1 inhibitors combined with chemotherapy significantly prolonged the lifespan of TNBC patients. The results of this study reveal that the activation of T cells in the TNBC microenvironment is closely related to tumor prognosis, and immunotherapy can improve the therapeutic effect of TNBC patients by regulating T cell activity. The research significance lies in providing new strategies for the precise treatment of TNBC, especially the broad application prospects of immunotherapy. In the future outlook, with the deepening understanding of the molecular mechanism and immune microenvironment of TNBC, as well as the development of new immunotherapy drugs, the prognosis of TNBC patients is expected to further improve, achieving more personalized and effective treatment plans.